MUDHARABAH AGRI-CROWDFUNDING IN THE EX-CLAY MINE UTILIZATION PROGRAM OF PT. SEMEN INDONESIA (PERSERO), TBK. CAMPUS OF C UNIVERSITAS INTERNASIONAL SEMEN INDONESIA - Tutuko, Bambang; Hudaifah, Ahmad; Asyhad, M.; Setyaningrum, Paramita; Cholilie, Irvan Adhin (Universitas Negeri Surabaya, 2019)
The objectives of research are to study market, technical, and financial feasibility of crowdfunding project using Syariah contract on specified agriculture project based on a higher education institute potency. Such process will be carried out to identify a feasibility of the land use in the project and the amount of funding needed to be collected with the concept of crowdfunding. The construction of a project requires analysis to determine the feasibility of the project. Method of research is quantitative by calculating financial feasibility. UISI has a land area of 3.8 hectares located on Campus of C UISI. This land is an ex-clay mining land of Semen Indonesia Company. Total investment and capital funding amount to Rp 100,000,000. The investment return period is 2 years. Based on the profit and loss calculation, it can be considered that capital and investment will return in the 6th month of the 1st year. In the 1st year the IRR obtained was 19%, whereas until the end of the second year the IRR was obtained by 42%. A significant difference occurred because in the second year Belimbing Tasikmadu, and Jambu Kristal fruit could already be harvested for commercial purpose.Â